The 2026 Muhammadiyah Fatwa and OJK Regulations on Crypto Assets: A Comparative Legal Analysis - Fajar Nuril Ilmi; Diantara Purnama; Theta Murty (Indonesian Journal of Law and Islamic Law (IJLIL), 2026)
This study analyzes the legal convergence and harmonization potential between the Muhammadiyah Fatwa of 2026 on crypto assets and OJK Regulation Number 27 of 2024 (POJK 27/2024) within Indonesia's national legal framework. Employing a normative juridical method with statutory and comparative approaches, this study examines two primary legal instruments: the Muhammadiyah Fatwa of 2026 issued by the Tarjih and Tajdid Council of the Muhammadiyah Central Committee, which reconceptualizes crypto assets through the māl mutaqawwam framework, and POJK 27/2024, which reclassifies crypto assets from commodities under Bappebti to digital financial assets under OJK supervision. The study finds three principal results. First, the Muhammadiyah Fatwa of 2026 permits crypto assets as tradable property when they cumulatively fulfill utility, digital storability, and social recognition through 'urf, while prohibiting their use as a means of payment and banning specific transaction mechanisms including futures trading, margin trading, short selling, and pump-and-dump practices. Second, POJK 27/2024 establishes binding obligations in governance, market integrity, and consumer protection, yet contains critical regulatory gaps, including the absence of a Sharia-based transaction classification, the absence of staking and airdrop regulations, and unresolved categorization inconsistencies that generate legal uncertainty for Muslim consumers. Third, the comparative analysis identifies four substantive convergences between the two instruments and proposes a three-pillar operational harmonization model: formal establishment of a Sharia-compliant crypto transaction classification within POJK 27/2024, institutionalization of periodic OJK–DSN-MUI coordination mechanisms, and mandatory Sharia-compliance disclosure obligations for licensed crypto asset traders. This model offers a concrete institutional pathway for integrating Islamic normative standards into Indonesia's positive legal framework, while positioning Indonesia as a reference model for Sharia-compliant crypto governance globally.